Effect of cooling methods on residual compressive strength and cracking behaviour of fly ash concretes exposed at elevated temperatures - Shaikh, Faiz; Vimonsatit, Vanissorn; Stewart, B.; Jack, F. (John Wiley and Sons Ltd., 2015)
This paper presents the effects of cooling methods on residual compressive strength and cracking behavior of concretes containing four different class F fly ash contents of 10%, 20%, 30% and 40% as partial replacement of cement at various elevated temperatures. The residual compressive strength of the aforementioned fly ash concretes is measured after being exposed to 200, 400, 600 and 800 °C temperatures and two different cooling methods, for example, slow cooling and rapid water cooling. Results show that the residual compressive strengths of all fly ash concretes decrease with increase in temperatures irrespective of cooling regimes, which is similar to that of ordinary concrete. Generally, control ordinary concrete and all fly ash concretes exhibited between 10% and 35% more reduction in residual compressive strength because of rapid cooling than slow cooling except few cases. Cracks are observed over concrete specimens after being exposed to temperatures ranging from 400 to 800 °C. Samples that are slowly cooled developed smaller cracks than those rapidly cooled. At 800 °C, all fly ash concretes that are exposed to rapid cooling showed the most severe cracking. X-ray diffraction analysis shows reduction of Ca(OH)2 peak and formation of new calcium silicate peak in concretes containing 20% and 40% fly ash when subjected to 800 °C in both cooling methods. Thermo gravimetric analysis and differential thermal analysis results show increase in thermal stability of concrete with increase in fly ash contents. The existing Eurocode also predicted the compressive strength of fly ash concretes with reasonable accuracy when subjected to the aforementioned elevated temperatures and cooling methods.